2003
DOI: 10.1049/el:20030886
|View full text |Cite
|
Sign up to set email alerts
|

Pipelined recursive modified Euclidean algorithm block for low-complexity, high-speed Reed–Solomon decoder

Abstract: A novel pipelined recursive modified Euclidean (ME) algorithm block for the low-complexity, high-speed Reed-Solomon (RS) decoder is presented. The deeply pipelined recursive structure enables implementation of a significantly low-complexity ME algorithm block with much improved clock frequency. The low-complexity, high-speed RS decoder using the pipelined recursive ME algorithm block has been implemented in 0.13 mm CMOS technology with a supply voltage of 1.1 V. The results show that it has significantly low h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Comparing (1)-(4) with (5)- (8), it can be observed that they are different only in the positions of R i and Q i , L i and U i , and a i and b i ; thus, a potential internal switch signal can transfer (5)-(8) to (1)-(4) when the degree of R i is smaller than the degree of Q i without l i . Moreover, since multiplying x |l i | can be implemented by the shift operation, if the needed shift signal can be generated by the internal finite-state machine (FSM),…”
Section: B Kes Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing (1)-(4) with (5)- (8), it can be observed that they are different only in the positions of R i and Q i , L i and U i , and a i and b i ; thus, a potential internal switch signal can transfer (5)-(8) to (1)-(4) when the degree of R i is smaller than the degree of Q i without l i . Moreover, since multiplying x |l i | can be implemented by the shift operation, if the needed shift signal can be generated by the internal finite-state machine (FSM),…”
Section: B Kes Blockmentioning
confidence: 99%
“…In [3], the BM algorithm is reformulated as reformulated inversionless BM (RiBM) with the same regular architecture format compared with the conventional ME algorithm [4], [5], and a folded BM algorithm based on RiBM is introduced in [6]. References [4], [7], and [8] implemented the conventional ME algorithm with systolic and recursive architectures, and [5] and [9] further implemented the ME algorithm with higher speed and lower hardware complexity. Recently, the degree computationless modified Euclidean (DCME) algorithm has been introduced in [ architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Note that [20] has better NAE value than our design but its NPE value is only 10% of our design. On the other hand, the ASIC-type the pipelined recursive RS architecture [22], [23] is very area-efficient with high data throughput rate (6160 Mb/s). Hence, it has a very high NAE value.…”
Section: ) Performance Comparisonmentioning
confidence: 99%